Acquisition of Language Proficiency in English Among Senior High School Students from the Different Strands - Kerny M. Macado; Felix M. Diano Jr. (Randwick International of Education and Linguistics Science Journal, 2021)
Using a quantitative-comparative design, this study compares the language proficiency of the Senior High School Students of a certain University from the five (5) different strands; Science-Technology-Engineering-Mathematics (STEM), Humanities-Education-Social Sciences (HESS or HUMSS), Business-Accountancy-Management (BAM or ABM), Technical-Vocational-Livelihood (TVL) and General Academic Strand (GAS) and determine on which of these strands excels in the language proficiency test. There are 40 students randomly selected per strand. They are tested using the Language Proficiency Test in English. The one-way Analysis of Variance was utilized in the study. The findings reveal that there is a significant difference (p<0.05) in the English language proficiency of the students from the five (5) strands. Moreover, the students from the STEM strand excel from the other strands. This further indicates that the STEM students are more superior and developed on the academic literacy, alternative understandings and adequate formulation of theories and concepts in dealing with different variations of linguistics skills.